2005
DOI: 10.1002/hyp.5776
|View full text |Cite
|
Sign up to set email alerts
|

Controls on runoff from a partially harvested aspen‐forested headwater catchment, Boreal Plain, Canada

Abstract: Abstract:The water balance and runoff regime of a 55 ha aspen-forested headwater catchment located on the Boreal Plain, Alberta, Canada (55Ð1°N, 113Ð8°W) were determined for 5 years following a partial timber harvest. Variability in precipitation provided the opportunity to contrast catchment water balances in relatively dry (<350 mm year 1 ), wet (>500 mm year 1 ), and average precipitation years. In most years, the catchment water balance was dominated by soil water storage, evapotranspiration losses, and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
169
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(181 citation statements)
references
References 35 publications
12
169
0
Order By: Relevance
“…Several studies address in part the connectivity between uplands and valleys, concluding that there is a temporally variable hydrologic connectivity between these two landscapes [52][53][54]. The hydrology subsystem in this study treats the upland watershed and the irrigated valley separately, but it also looks at key interactions between these two landscapes.…”
Section: System Function and Causality For Diagrammentioning
confidence: 99%
“…Several studies address in part the connectivity between uplands and valleys, concluding that there is a temporally variable hydrologic connectivity between these two landscapes [52][53][54]. The hydrology subsystem in this study treats the upland watershed and the irrigated valley separately, but it also looks at key interactions between these two landscapes.…”
Section: System Function and Causality For Diagrammentioning
confidence: 99%
“…Thus, on the western Boreal Plain of Alberta (where PPT<PET and there is often little or no annual runoff ), critical hydrologic indicators might be soil water storage and the direction of groundwater flux between hillslopes and wetlands (Devito et al, 2005a), whereas on the eastern Boreal Shield of Quebec (where PPT>PET and there is always annual runoff ) critical indicators might include peak and low streamflows (Guillemette et al, 2005;Sanford et al, 2007). Buttle (2006) presented a template for assessing the interactive effects of the dominant controls on basin streamflow in a given HRU.…”
Section: Progress In Understanding and Classifying Hydrologic Systemsmentioning
confidence: 99%
“…On the Boreal Plain of northern Alberta, a five year study following a partial harvest of an aspen forest basin showed that soil water storage and vertical fluxes (ET and recharge) drive the water balance in most years, such that upland soil water storage capacity resulting in hydrologic connection of upland and lowland areas and significant runoff production is exceeded only about once in 20 years (Devito et al, 2005a). Runoff source areas were restricted to ephemeral draws and/or wetlands-which would be susceptible to harvesting effects during most years-and were therefore identified as priority areas for protection.…”
Section: Forest Management Practices That Emulate Natural Disturbancementioning
confidence: 99%
“…This followed an earlier Moose Lake catchment (0.5 km 2 ) study where post-harvest aspen vs. non-harvest sub-catchments were examined. This study illustrated the influence of soil moisture, groundwater storage, and climate variability on threshold runoff responses (Devito et al 2005a(Devito et al , 2005b.…”
Section: Introductionmentioning
confidence: 61%
“…As part of this approach, the 2006 Al-Pac Forest Management Plan proposed to concentrate harvest activities in a given area for a 10-15 year period resulting in larger disturbance events with unknown effects on the hydrologic processes at a catchment or landscape scale. The regional moisture deficit (P < PET), large spatial heterogeneity of deep glacial deposits (outwash sands to lacustrine clay), and seasonal and decadal wet and dry cycles in the boreal plains region (Devito et al 2005c) result in: a) dynamic and complex surface and groundwater interactions; and, b) potentially large temporal and spatial variability in the sensitivity of forest and stream ecosystems to local and regional disturbance (Devito et al 2005a, Macrae et al 2005, 2006CarreraHernandez et al 2011aCarreraHernandez et al , 2011b.…”
Section: Introductionmentioning
confidence: 99%